Effectiveness of the Role of Epidemiological Surveillance in the Management of Communicable Diseases and Immunization-Preventable Diseases (PD3I) in Serang District - Yeni Susanti; Rahmat Supriyatna (Jurnal EduHealth, 2025)
Epidemiological surveillance is currently a very important element in facing the challenges of managing infectious diseases that continue to grow. Infectious diseases such as dengue fever (DHF), tuberculosis (TB), and new emerging or re- emerging diseases pose a serious threat to public health (MOH, 2024) . At the local level, such as in Serang District, weaknesses in the surveillance system can hinder the control of infectious diseases that have dynamic patterns of spread. The findings in the field are (a) the high incidence of infectious diseases which are still a serious challenge for the community. Diseases such as dengue, tuberculosis, and diarrhea continue to show incidence patterns that require special attention. (b) Epidemiological surveillance is a very important tool in detecting, monitoring and responding to the spread of disease quickly and accurately. The purpose of the study was to identify the strengths, weaknesses, opportunities, and threats that exist in the organizational plan and examine the external environment and to identify opportunities and threats to the epidemiological surveillance program in controlling infectious diseases and PD3I in Serang District. This research uses a qualitative approach with interview and observation methods. The strategies carried out are supporting DHO policies, increasing the use of information technology to accelerate information, and coordination with stakeholders related to infectious diseases and PD3Is. Then the need for appropriate technological innovation in the use of applications, the need for regular training, and adding technological infrastructure such as computers and cell phones. And the need for coordination with other related agencies, new disease information to be fast, and coordination with the promkes section. As well as remote health facilities need to be fostered regularly and the use of technology in an appropriate manner.